Effect of the mismatch structure on crystal packing, physical properties and third-order nonlinearity of unsymmetrical twistacenes. (November 2016) - Chen, Shulian; Xiao, Jinchong; Zhang, Xi; Shen, Xingxing; Liu, Xiaoyu; Shen, Fugang; Yi, Yuanping; Song, Yinglin
Abstract: A novel family of unsymmetrical twistacene analogues were synthesized in a palladium-promoted cross-coupling reaction and fully characterized, where five-membered ring was embedded into the main skeleton int hese molecules. The formed all-carbon compounds appreciate a series of promising photophysical properties such as good thermal stability and photostability than that of acenes consisting of all six-membered rings. All of them emitted strong solution fluorescence covered a wide range from cyan to yellow. In addition, the nonlinear optical properties were further investigated through the top-hat Z-scan technique at 515 nm, which indicates that all of them presented excellent third-order nonlinear absorption effects. Graphical abstract: Five-membered ring-embedded unsymmetrical twistacenes were prepared that presented large third-order nonlinearity. Highlights: Five-membered ring-embedded unsymmetrical twistacenes were prepared. The formed molecules show high thermal stability and strong blue, green and yellow fluorescence. These molecules exhibited large third-order nonlinearity, which could be utilized in optical devices.